Cognition and BDNF levels in prediabetes and diabetes: A mediation analysis of a cross-sectional study - Sumbul-Sekerci, Betul; Sekerci, Abdusselam; Pasin, Ozge; Durmus, Ezgi; Yuksel-Salduz, Zeynep Irem (Frontiers in Endocrinology, 2023)
Aim: Clinical and epidemiological studies suggest links between dementias and Type 2 diabetes (T2DM). The underlying mechanisms of diabetes-related cognitive impairment are largely unknown. This study aims to investigate the role of BDNF in cognitive impairment in prediabetes and T2DM. Methods: The study included 68 patients with prediabetes (preDM), 96 patients with T2DM, and 65 healthy controls. The cognitive function of the patients was evaluated with the Montreal Cognitive Assessment (MoCA) test and serum BDNF levels were measured by Elisa. The MoCA scores and BDNF levels were compared between diabetes groups after adjusting for age, gender, and education using ANCOVA. The role of BDNF in diabetes-related cognitive impairment was investigated through mediation analysis. Results: Patients with T2DM had significantly lower cognitive performance, particularly in memory. Diabetes was found to be a predictor of both cognitive impairment and BDNF levels. A significant increase in serum BDNF levels was observed in patients with T2DM. However, the mediator role of BDNF in the pathology of cognitive impairment in diabetes was not determined. Conclusion: Cognitive impairment is prevalent in patients with T2DM and should be included in routine screening for complications. The results of the mediation analysis suggest that although BDNF is a biomarker affected by T2DM and cognition, it does not play a mediator role between cognitive impairment and diabetes.